Personnel economics for managers - Lazear, Edward P. (New York : John Wiley and Sons, 1998)
Introduction. Setting hiring standards. Hiring the right people. Learning a worker's productivity. Variable pay or straight salary? The theory of human capital...
Keywords: Economics; Management; Labor economics; Personnel management; Managerial economics; Labor economics; Human capital